Determination of illegal antimicrobials in aquaculture feed and fish: An ELISA study. (April 2015) - Oliveri Conti, Gea; Copat, Chiara; Wang, Zhanhui; D'Agati, Placido; Cristaldi, Antonio; Ferrante, Margherita
Abstract: Antimicrobials are added to the feed or drinking water of food-producing animals to reduce susceptibility to infection, accelerate weight gain, or reduce the amount of food required to gain weight. Some compounds have been banned for food safety reasons, for other agents the U.S. Food and Drug Administration (FDA) is implementing a plan with industry to phase out a number of antibiotics. The concentrations of crystal violet (CRY), chloramphenicol (CAP), gentamicin (GEN), fluoroquinolone-enrofloxacin (FQ), malachite green (MG), and the metabolites of furaltadone (FU) and furazolidone (FZ) antibiotics (respectively AMOZ and AOZ) were determined in 30 samples both feed and fish from an aquaculture farm in eastern Sicily (Italy) using commercial ELISA Kits. Levels exceeding the method's detection capability were found in all feed and tissue samples. Feed contained all the analytes tested; GEN, CRY and CAP showed the highest mean concentrations, respectively 31.8, 4.05 and 3.67 μg kg −1 . The mean concentrations of CAP, CRY, FQ, MG, AMOZ and AOZ in muscle were 0.57, 2.05, 0.14, 0.48, 0.29 and 0.09 μg kg −1, respectively (the assay was not certified to determine GEN in muscle). The higher levels detected in feed are explained by the fact that 50% of farmed fish is used to make fish meal, thus compounding bio-accumulation. Our data show that aquaculture feed and fish contain banned antimicrobials. Consumption of farmed fish may therefore involve a risk for consumers, besides contributing to the growth of antibacterial resistance. Surveys of larger feed and fish samples are needed to achieve a more reliable assessment of consumer risk. Highlights: We assessed antimicrobials in feed and fish from an aquaculture through ELISA. The performance characteristic of methods were described. Levels exceeding the method's detection capability were found in all samples. The 50% of farmed fish is used to make fish meal, thus compounding bio-accumulation. Results were important because data on this topic are still today scarce.